Nivel de autoestima y habilidades sociales en adolescentes del Centro de Estudios Preuniversitarios Universidad Nacional de Trujillo. 2020 - Cruzado Coronado, Nitzy Nicol (2021)
The present quantitative applied descriptive correlation research was aimed at establishing the relationship between the level of self-esteem and social skills in adolescents from the Pre-university Center of the National University of Trujillo, 2020. The sample consisted of 161 adolescents, who comply with the established inclusion criteria. Two instruments were applied for data collection: the first Self-Esteem Level questionnaire by Cooper Smith and the second questionnaire is the test to assess the Level of Social Skills that was developed by Goldstein. The results were that self-esteem was high in 42.9% of students, medium in 50.3% and low in 6.8%. Regarding social skills, 44.7% presented a high level, 46.6% medium social skills and 8.7% low, with a significant statistical relationship between the level of self-esteem and social skills.